Impact of Combine Dithering and Modulators to Mitigate Noise in Radio Over Fiber System - Fakhriy Hario; Eka Maulana; Hadi Suyono; Rini N Hasanah; Sholeh H Pramono (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
A well-prepared Radio over Fiber (RoF) is a technology that combines two transmission technologies, radio and optical fiber transmissions. The study focused on the characteristics and problems of the optical fiber medium. One of the problems in the optical fiber is the effect of nonlinear characteristic, which caused by the high light intensity in the optical fiber core with extended interaction area in a single mode fiber (SMF). This characteristic reduces the output width and creates a pulse broadening. The nonlinear characteristics discussed in this study focused on SPM (self-phase modulation) and GVD (Group Velocity Dispersion). To overcome the nonlinear problems, this study presented a method to make the noise-resistant transmitted signal and improve the optical fiber power range. The fundamental of this study was developing similarities of previous studies regarding nonlinearity in the optical fiber. The results show that the use of two modulators combined with the amplification generated the signal with smoother spectrum, which means that the spectrum distribution was more uniform. There was 61.5 % increase of the peak power of the output signal after amplification using an optical amplifier.